2007
DOI: 10.1099/mic.0.2007/010231-0
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the regulation of the Saccharomyces cerevisiae UGA4 gene: two parallel pathways participate in carbon-regulated transcription

Abstract: The Saccharomyces cerevisiae UGA4 gene, which encodes the c-aminobutyric acid (GABA) and d-aminolaevulinic acid (ALA) permease, is well known to be regulated by the nitrogen source. Its expression levels are low in the presence of a rich nitrogen source but are higher when a poor nitrogen source is used. In addition, GABA can induce UGA4 expression when cells are grown with proline but not when they are grown with ammonium. Although vast amounts of evidence have been gathered about UGA4 regulation by nitrogen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Gln3 transcription factor is important for the transactivation of the UGA4 gene in response to GABA (André et al, 1995;Luzzani et al, 2007), whereas its importance for UGA1 induction is controversial. While Talibi et al (1995) reported a 60 % reduction of UGA1 induction in the absence of Gln3, Daugherty et al (1993) reported that this GATA factor does not participate in UGA1 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Gln3 transcription factor is important for the transactivation of the UGA4 gene in response to GABA (André et al, 1995;Luzzani et al, 2007), whereas its importance for UGA1 induction is controversial. While Talibi et al (1995) reported a 60 % reduction of UGA1 induction in the absence of Gln3, Daugherty et al (1993) reported that this GATA factor does not participate in UGA1 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The UAS GABA mut-lacZ fusion gene contains the UGA4 sequence, positions Ϫ583 to ϩ15 with respect to the ATG initiation codon, with an altered UAS GABA element, where the core sequence GCCGGCGGC was replaced by ATTAGTAAT (the changed positions are underlined). All these constructions were previously described by Luzzani et al (33). The UAS GABA del-lacZ fusion gene generated using the strategy described by Strachan and Read (38a) contains the UGA4 sequence, positions Ϫ583 to ϩ15 with respect to the ATG initiation codon, with the sequence GCCGGCGGC deleted from the UAS GABA element.…”
Section: Plasmidsmentioning
confidence: 99%
“…The sequence obtained after amplification with primer P7 has shown higher similarity (78%) to the protein sequence of a gamma-aminobutiric acid (GABA) transport protein of Candida albicans . In Sacharomyces serevisiae , the UGA4 gene, which showed homology to GABA/polyamine transporter gene from C. albicans , encodes the gamma-aminobutyric acid (GABA) and δ-aminolaevulinic acid (ALA) permease and its expression is regulated by the N and C source (31). The UGA4 protein is located at the vacuolar membrane and catalyses the transport of the gamma-aminobutyric acid (GABA) and putrescine (53).…”
Section: Resultsmentioning
confidence: 99%
“…The UGA4 protein is located at the vacuolar membrane and catalyses the transport of the gamma-aminobutyric acid (GABA) and putrescine (53). The gamma-aminobutyric acid (GABA) transport protein in S. serevisiae supports cell growth with the GABA as the sole N source and, therefore, may also be related to adaptation to starvation (31, 53). It was demonstrated that the expression of the UGA 4 gene is repressed by extracellular amino acids and is mediated by a multicomponent amino acid sensor complex known as SPS sensor, localized at the plasma membrane (34).…”
Section: Resultsmentioning
confidence: 99%